2012
DOI: 10.1136/bjophthalmol-2012-301947
|View full text |Cite
|
Sign up to set email alerts
|

Long term visual outcomes, graft survival and complications of deep anterior lamellar keratoplasty in patients with herpes simplex related corneal scarring

Abstract: DALK for the treatment of HSV related corneal scarring is associated with a high percentage of postoperative complications. DALK in this context is also associated with a large percentage of secondary operations. Patients should be aware of this when giving informed consent for DALK to treat HSV related corneal scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Recent advances in corneal transplantation techniques with a shift from penetrating to safer lamellar procedures and wide application of limbal epithelial stem cell transplantation, have resulted in improved outcomes, and have expanded the number of cases of corneal blindness that can now be treated successfully . However, patients with severe pathologies (e.g., chemical burns, previously rejected grafts, autoimmune disease, and infections) still have a high risk of rejection and failure, often needing multiple surgeries . Corneal prostheses are available, but they remain mainly for end‐stage disease and even if implanted as primary procedure they often are accompanied by vision‐threatening complications, leaving an unmet need for a de novo solution for high‐risk patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in corneal transplantation techniques with a shift from penetrating to safer lamellar procedures and wide application of limbal epithelial stem cell transplantation, have resulted in improved outcomes, and have expanded the number of cases of corneal blindness that can now be treated successfully . However, patients with severe pathologies (e.g., chemical burns, previously rejected grafts, autoimmune disease, and infections) still have a high risk of rejection and failure, often needing multiple surgeries . Corneal prostheses are available, but they remain mainly for end‐stage disease and even if implanted as primary procedure they often are accompanied by vision‐threatening complications, leaving an unmet need for a de novo solution for high‐risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, patients with severe pathologies (e.g., chemical burns, previously rejected graft s, autoimmune disease, and infections) still have a high risk of rejection and failure, oft en needing multiple surgeries. [3][4][5][6][7][8] Corneal prostheses are available, but they remain mainly for end-stage disease and even if implanted as primary procedure they oft en are accompanied by visionthreatening complications, 1,9 leaving an unmet need for a de novo solution for high-risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] In addition to the obvious advantage of absence of endothelial graft rejection, DALK allows the use of poor-quality donor corneas thereby alleviating the problem of shortage of donor corneas in the developing world. 20,21 Considering these factors, we performed DALK for patients with deep HSKinduced corneal scars with functional endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported encouraging outcomes of DALK in treating HSK-related corneal scarring in which posterior lamella and endothelium were not compromised. [14][15][16] These reports indicated that the depth of the scar should not exceed two thirds of the stroma. In this study, we report the long-term outcomes of DALK in deep stromal HSK-related corneal scars with or without associated posterior stromal folds approaching the endothelium.…”
mentioning
confidence: 93%
“…DALK shows comparable visual outcome and better graft survival rate than PK , though there is a high percentage of complications post‐DALK …”
Section: Prevention Of and Treatment For Corneal Diseasementioning
confidence: 99%